1979
DOI: 10.1111/j.1471-0528.1979.tb10590.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Prostaglandin‐induced Uterine Activity by Nifedipine

Abstract: The effects of the calcium antagonist, nifedipine, on uterine activity induced by prostaglandins F,, (PGFZa) and E, (PGE,) were studied in women undergoing therapeutic midtrimester abortion, and in patients with a missed abortion in the 16th to 27th week of pregnancy. In the five subjects receiving intra-amniotic PGF,, (25 to 40 mg) for midtrimester abortion, nifedipine (30 mg orally) decreased uterine activity from a mean of 372 to 203 Montevideo Units. The effect on the intensity of the contractions was pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…Fourteen days' treatment with nifedipine may be less than the optimal period for evaluation (Cocco et al, 1979), and in the present group of patients, no anti-anginal benefit was observed in some patients, whilst others demonstrated significant subjective and objective improvement, confirming earlier work (Hollmann et al, 1975). Nifedipine has been reported as relieving spasm in visceral smooth muscle in vivo in the uterus (Ulmsten, Andersson and Forman, 1978;Andersson et al, 1979), oesophagus (Weiser et al, 1977;Blackwell, Holt and Heading, 1979), and urinary tract (Forman et al, 1978). The authors cannot explain the increase in PEFR alone following a single dose of nifedipine, without there being an effect on FEV, or FVC, and further work is required to elucidate this point.…”
Section: Discussionsupporting
confidence: 83%
“…Fourteen days' treatment with nifedipine may be less than the optimal period for evaluation (Cocco et al, 1979), and in the present group of patients, no anti-anginal benefit was observed in some patients, whilst others demonstrated significant subjective and objective improvement, confirming earlier work (Hollmann et al, 1975). Nifedipine has been reported as relieving spasm in visceral smooth muscle in vivo in the uterus (Ulmsten, Andersson and Forman, 1978;Andersson et al, 1979), oesophagus (Weiser et al, 1977;Blackwell, Holt and Heading, 1979), and urinary tract (Forman et al, 1978). The authors cannot explain the increase in PEFR alone following a single dose of nifedipine, without there being an effect on FEV, or FVC, and further work is required to elucidate this point.…”
Section: Discussionsupporting
confidence: 83%
“…Calcium channel blockers such as nifedipine have been researched extensively as tocolytics [23]. Nifedipine was introduced in 1977 appear to be among the more efficacious and safer drugs that are currently being used for tocolysis [24], but the lack of good quality evidence available for these tocolytics and reports of cardiovascular side effects may limit their usefulness in the treatment of preterm labor.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Fourteen days' treatment with nifedipine may be less than the optimal period for evaluation (Cocco et al, 1979), and in the present group of patients, no anti-anginal benefit was observed in some patients, whilst others demonstrated significant subjective and objective improvement, confirming earlier work (Hollmann et al, 1975). Nifedipine has been reported as relieving spasm in visceral smooth muscle in vivo in the uterus (Ulmsten, Andersson and Forman, 1978;Andersson et al, 1979), oesophagus (Weiser et al, 1977;Blackwell, Holt and Heading, 1979), and urinary tract (Forman et al, 1978). The authors cannot explain the increase in PEFR alone following a single dose of nifedipine, without there being an effect on FEV, or FVC, and further work is required to elucidate this point.…”
Section: Discussionmentioning
confidence: 99%